SANTRI DAN ABANGAN DALAM KEHIDUPAN KEAGAMAAN ORANG JAWA - Adib Fathoni (At-Taqaddum, 2012)
Students of Pesantren (Santri) and “abangan” is a unique and distinctive terms of Java. Although the two terms are not equally used by the Javanese, but in essence is to identify Javanese muslims who obey Islamic law (students/santri) and who do not obey (‘abangan’).In daily life, the student/santri and the people abangan interrelated and each draw positive perception of one another. Students suppose that isn’t  unbeliever/kavir, but muslims are not steeped in the teaching of Islam seriously, because it had not reached them enlightenment and understanding of thouse teachings, The variation of student/santri –abangan caused by defferences due to the wave of Islamization and geographical distribution. Thus when observed  further, it will show the areas where it is made up of the majority of santri/student, or people abangan, or a maxture of both, in the areas of java ; coastal area of relatively santri and interior/hinterland areas of relatively abangan but now the map has changed, Indeed, historically, our civilization in Java is more than the shear sliding, impact and incluence, between the cultural hinterland and the coastal culture, this accurs more prominently and associated as the attraction between the Islamic agricultural tradition rooted the elements of indigenous and pre-Islamic.